Developing an optimization tool for evaluating the transmission system expansion - Forti Da Silva, Tiago [UNESP]; Nunes De Souza, Andre [UNESP]; Da Costa Junior, Pedro [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2015)
The transmission system is responsible for connecting the power generators to consumers safely and reliably , its constant expansion is necessary to transport increasing amounts of electricity. In order to help the power systems engineers, an optimization tool for optimize the expansion of the transmission system was developed using the modeling method of the linearized load flow and genetic. This tool was designed to simulate the impact of different scenarios on the cost of transmission expansion. The proposed tool was used to simulate the effects of the presence of distributed generation in the expansion of a fictitious transmission system, where it was found a clear downward trend in investment required for the expansion of the transmission system taking account of increasing levels of distributed generation.
Keywords: Genetic Algorithms; Power System Planning; Transmission Lines